2013
DOI: 10.1177/1010539512471075
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Correlated With Risk of Insulin Resistance Using Homeostasis Model Assessment in Adolescents in Taiwan

Abstract: The study aims to discover risk factors significantly correlated with insulin resistance among adolescents in Taiwan. A total of 339 study subjects were recruited in this cross-sectional study. A self-administered questionnaire and physical examinations including anthropometrics and biochemistry profiles were collected. Insulin resistance was assessed using homeostasis model assessment for insulin resistance (HOMA-IR). Study subjects had a significantly increased risk of IR for those with abnormal level of bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…Our findings are largely concordant with evidence from a previous study showing that maternal age, BMI, and excessive weight gain before 24 weeks of gestation are risk factors for the development of GDM and IR . A study conducted among general population in Taiwan demonstrated a significantly increased risk of IR for people with abnormal BMI . In line with our study, increased prepregnancy BMI and weight gain before diagnosis of GDM were significantly associated with increased risk of higher IR in the second trimester.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are largely concordant with evidence from a previous study showing that maternal age, BMI, and excessive weight gain before 24 weeks of gestation are risk factors for the development of GDM and IR . A study conducted among general population in Taiwan demonstrated a significantly increased risk of IR for people with abnormal BMI . In line with our study, increased prepregnancy BMI and weight gain before diagnosis of GDM were significantly associated with increased risk of higher IR in the second trimester.…”
Section: Discussionsupporting
confidence: 92%
“…18 A study conducted among general population in Taiwan demonstrated a significantly increased risk of IR for people with abnormal BMI. 19 In line with our study, increased prepregnancy BMI and weight gain before diagnosis of GDM were significantly associated with increased risk of higher IR in the second trimester. In the RADIEL trail, 20 293 women with history of GDM or a prepregnancy BMI of >30 kg/m 2 were enrolled and divided into two groups.…”
Section: Discussionsupporting
confidence: 90%
“…As Lin et al (2015) also highlighted, the close association between these anthropometric variables and BP levels in relation to abnormal HOMA-IR values (i.e., their combined effect) indicates that this relationship should be regarded as a predictive risk factor for insulin resistance. Similar to Reaven's (2004) study, our results show the effects of BMI, body fat percentage, WC, and systolic BP levels, factors that heighten the risk of an abnormal HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the crosssectional nature of this study limits our ability to detect causal relationships between each of the factors analyzed and the possible development of insulin resistance. In this sense, and as Lin et al (2015) underlined, future studies should focus on the monitoring and evaluation over time of all the potentially influential factors and circumstances in the genesis of MetS at an early age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation